Separate analysis of human papillomavirus E6 and E7 messenger RNAs to predict cervical neoplasia progression. - Shuling Liu; Takeo Minaguchi; Bouchra Lachkar; Shuang Zhang; Chenyang Xu; Yuri Tenjimbayashi; Ayumi Shikama; Nobutaka Tasaka; Azusa Akiyama; Manabu Sakurai; Sari Nakao; Hiroyuki Ochi; et al. (PLoS ONE, 2018)
A few studies previously suggested that human papillomavirus (HPV) E6 messenger RNA (mRNA) may exist uniformly in all grades of cervical intraepithelial neoplasia (CIN), whereas the detection rate of E7 mRNA may increase with disease progression from low-grade CIN to invasive carcinoma. The aim of this study was to clarify the different roles of E6 and E7 mRNAs in cervical carcinogenesis. The presence of each E6 and E7 mRNA was analyzed in 171 patients with pathologically-diagnosed CIN or cervical carcinoma. We utilized a RT-PCR assay based on consensus primers which could detect E6 mRNA (full-length E6/E7 transcript) and E7 mRNAs (spliced E6*/E7 transcripts) separately for various HPV types. E7 mRNAs were detected in 6% of CIN1, 12% of CIN2, 24% of CIN3, and 54% of cervical carcinoma. The presence of E7 mRNAs was significantly associated with progression from low-grade CIN to invasive carcinoma in contrast with E6 mRNA or high-risk HPV (HR-HPV) DNA (p = 0.00011, 0.80 and 0.54). The presence of both E6 and E7 mRNAs was significantly associated with HPV16/18 DNA but not with HR-HPV DNA (p = 0.0079 and 0.21), while the presence of E6 mRNA was significantly associated with HR-HPV DNA but not with HPV16/18 DNA (p = 0.036 and 0.089). The presence of both E6 and E7 mRNAs showed high specificity and low sensitivity (100% and 19%) for detecting CIN2+ by contrast with the positivity for HR-HPV DNA showing low specificity and high sensitivity (19% and 89%). The positive predictive value for detecting CIN2+ was even higher by the presence of both E6 and E7 mRNAs than by the positivity for HR-HPV DNA (100% vs. 91%). In 31 patients followed up for CIN1-2, the presence of both E6 and E7 mRNAs showed significant association with the occurrence of upgraded abnormal cytology in contrast with E6 mRNA, HR-HPV DNA, or HPV16/18 DNA (p = 0.034, 0.73, 0.53, and 0.72). Our findings support previous studies according to which E7 mRNA is more closely involved in cervical carcinogenesis than E6 mRNA. Moreover, the separate analysis of E6 and E7 mRNAs may be more useful than HR-HPV DNA test for detecting CIN2+ precisely and predicting disease progression. Further accumulation of evidence is warranted to validate our findings.